The blue dog challenges in marketing a prevention message. (1st March 2011) - De Keuster, T; Butcher, R; Van Laeken, M
Abstract : Dog bite injuries are a significant cause of injuries to children (between 3 7 years of age) within the home. Although dog-related factors are important, the behaviour of the potential victim is a key issue. The Blue Dog programme, which takes the form of an interactive CD-ROM, was developed to educate children and their parents to recognise risk situations within the home and avoid them. Since the launch in 2004, difficulties have been experienced in attempting to promote dog bite prevention messages both to the end-user and potential sponsors, feedback indicating fear control may be a contributory factor in message rejection. This was further highlighted in an independent marketing review. An extensive redevelopment of the website has been undertaken to minimise fear appeals so improving chances of message acceptance. The design is intended to be attractive to parents and children. While searching for positive information (or indeed playing games) it is hoped that they will become introduced to the potential risks and accept the prevention message within the overall balanced package. In addition, the website will provide information and downloadable resources free of charge for health professionals and school teachers. The wide range of information to be included on the website will provide scope to offer partnerships to a large number of associated groups. This will expand the network of organisations associated with the programme and may help to attract additional commercial funding. It is intended to launch the new website in September 2010, though this will continue to evolve.